Accumulating biological capital through the commodification of women: a historical appreciation of the commercialization of lobola/roora in Zimbabwe 1920-2010. - Tarugarira, Gilbert; Mazambani, Ishmael (Midlands State University, 2016)
There has been much disputation over the radical transformation of lobola into a commercial pursuit in Zimbabwe. Studies on lobola have largely focused on how this practice is conducted and the cultural significance attached to it. The unexplored dimension in the academic fraternity has been tracing how changing socio-economic and political environments led to the commodification of women and the commercialization of lobola. Rather than becoming a swallowing monster, lobola has grown in the same proportion as the growing body and wealth of African society. This study reveals how lobola has kept pace with the march of time, showing resilience against attacks from the outside and within, and flexibility for adapting itself to changing conditions dictated by the pre- colonial, the colonial and post-colonial socio-economic environments. The contention is that fluctuations in lobola charges should be understood within the context of the dictates of the multifaceted socio-economic and political frameworks. The colonial policies created their own demands while the post-colonial challenges accelerated the commercialization of lobola.